Microwave radiation and its application on construction materials. Issue 4 (1st October 2016) - Procházka, Martin; Sobotka, Jindřich; Šuhajda, Karel; Novotny, Miloslav
Abstract: Drying structures using high-frequency electromagnetic radiation or microwave technology is currently gaining much more usage in the engineering practice. The goal of the method is the quickest elimination of water in construction (wall, floor structure, etc.). Microwave is a part of the electromagnetic radiation of frequency between 300 MHz and 300 GHz and wavelength between 1 mm and 1 m. The frequency of 2.45 GHz and 122 mm wavelength is used for engineering practice. Due to the effect of microwave radiation the divergent homogeneity of temperature field of different building materials can be observed. This article discusses the spread of thermal field depending on the volume of water and thereby the size of mass humidity of the given material (timber). The temperature fields will be observed by a thermo camera, always after a certain time cycles of the heating.